Communication Strategies of School Principals for Effective School Management: A Literature Review - Simatupang, Umy Nadrah; Marsidin, Sufyarma; Sulastri, Sulastri (Postgraduate School, Universitas Negeri Padang, 2024)
Education is a multifaceted process encompassing cognitive, affective, and physical-motor development crucial for individual and societal advancement. The quality of education relies heavily on esteemed school institutions that guide educational initiatives toward positive outcomes. However, Indonesia's current educational landscape reveals diverse perceptions of educational quality, exposing a gap between community expectations and expert evaluations. In response to these challenges, school principals play a pivotal role in promoting effective school management through adept leadership and strategic communication. This literature review examines the attributes of effective school management, emphasizing the leadership responsibilities of school principals in Indonesia. Key components include defining educational objectives clearly, implementing structured learning approaches, and fostering inclusive stakeholder engagement. Additionally, the study highlights communication as pivotal in enhancing organizational coherence and achieving educational goals. Through an analysis of existing literature, this paper advocates for customized communication strategies by school principals to enhance school management effectiveness, contributing to the discourse on educational leadership and management practices in Indonesia.